The Effect of Traditional Congklak Game Method on Students' Learning Outcomes in Learning Mathematics in Elementary Schools - Fatimatuszahro Fatimatuszahro; Heni Hanifah; Lily Hermawanti; Sri Wahyuni; Rasilah Rasilah (MASI Mandiri Edukasi, 2025)
Every level of education includes mathematics as one of its disciplines. However, due to ineffective teaching, children find mathematics less interesting in elementary school. Therefore, teachers must be able to choose the best teaching strategy for their students. By utilizing the classic congklak game, researchers hope to deliver learning media that teachers can use using a literature review study approach from various sources and related media. The analysis findings show that, in addition to helping children learn to count and recognize numbers, the classic congklak game also helps children develop moral principles and good behavior, such as the ability to act honorably, wisely, and obediently. The traditional congklak game can increase students' interest in learning. The traditional Congklak game is also considered one of the most effective ways of improving students' mathematical abilities. So, this game can be used as a reference for teaching mathematics methods. Thus, the traditional congklak game changes mathematics into something exciting and fun to learn.